Examination of Athletic Identity and Exercise Regulation Motivation After Sport Retirement - Craig, Lauren (My University, 2017)
This study sought to fill several gaps in the current exercise motivation literature by utilizing self-determination theory and identity theory in exploration of the relationship between athletic identity, exercise identity, and exercise motivation on perceived psychological need fulfillment and overall quality of life among NCAA retired collegiate athletes. To date, several studies have explored motivations for long-term exercise maintenance, but have predominately focused on inconsistently active individuals (Brunet & Sabiston, 2011; Burns et al., 2012) or current competitive athletes (Adler & Adler, 1991; Amorose & Horn, 2000, 2001; Brewer, Van Raalte, & Linder, 1993). Additionally, minimal attention has focused on distinguishing between athletic identity and exercise identity and how these statuses may evolve over time. Consequently, exercise motivations and the impact of athletic identity and exercise identity on long-term engagement in exercise for retired collegiate athletes served as the focus for the current study. Results revealed participants’ exercise identity significantly predicted scores on psychological need fulfillment, and participants’ athletic identity significantly predicted scores on perceived quality of life. Additionally, results indicated self-determined motivations for exercise significantly predicted higher levels of both psychological need fulfillment and quality of life. Women reported significantly higher exercise identity scores when compared to men participants, and participants who competed at the Division I level reported significantly higher exercise identity scores when compared to participants who competed at Divisions II and III. Strengths and limitations of the study are discussed and areas for further research are posited.
Keywords: athletic identity; sport retirement; behavioral regulation; self-determination